Proverbs with God in Don Quixote de la Mancha: a study compared with contemporary religious texts - Fernández Martín, Patricia (Romanica Olomucensia, 2025)
The aim of this paper is to make a comparison between the use of the proverbs with the term God in Don Quixote de la Mancha and a set of religious texts also belonging to the Spanish Golden Age. The Coserian concept of a "universe of discourse" is taken as a basis in order to distinguish between the world of reference of literature, on the one hand, from that of faith, on the other. To achieve this, the proverbs in the novel Don Quixote de la Mancha that contain the term God are taken as a reference and, as a consequence, searched for in CORDE texts published between 1500 and 1699 with religious themes (biblical texts and glosses, Bibles, glosses of the Bible, hagiography, mysticism and ascetic, catechetical, sermon). Quantitatively, eight out of the 17 proverbs recorded in Don Quixote appear in the selected religious corpus too. Qualitatively, the different forms and peculiar values of the proverbs show some internal differences between religious discourses and the selected literary discourse. The differences found between the proverbs with God in the literary discourse and in the religious discourse of the Golden Age demonstrate, first, the Coserian interrelation between the discursive universes and the worlds of knowledge that they expose and, second, the socio-cognitive interrelation that takes place between the expectations generated by the texts among readers and the knowledge that the respective writers share with them.
Keywords: Spanish literature; Spanish Golden Age; discourse universes; religion